THE ROLE OF WORK MOTIVATION AND TRANSFORMATIONAL LEADERSHIP ON ENHANCING EMPLOYEE ENGAGEMENT - Ahmad Syauqi; Susanto Susanto; Obing Zaid Sobir; Ramdan Yusuf; Dipa Teruna Awaludin (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the role of Work Motivation and Transformational Leadership in enhancing employee engagement  in private companies. Using a quantitative research approach, data were collected from 100 employees through a purposive sampling technique. The data were analyzed using partial least squares (PLS) regression, assisted by SmartPLS version 3.29. The results reveal that work motivation has a significant positive effect on employee engagement, indicating that employees who experience a better work environment and balance tend to be more engaged in their work. In contrast, Transformational Leadership do not have a significant impact on employee engagement. These findings suggest that private companies seeking to increase employee engagement should not rely solely on leadership factors,but should also focus on developing strong organizational motivation that strengthens engagement at all levels of the organization.